Micelle-Assisted Synthesis of Al2O3·CaO Nanocatalyst: Optical Properties and Their Applications in Photodegradation of 2, 4, 6-Trinitrophenol. (7th November 2013) - Imtiaz, Ayesha; Farrukh, Muhammad Akhyar; Khaleeq-ur-rahman, Muhammad; Adnan, Rohana
Abstract : Calcium oxide (CaO) nanoparticles are known to exhibit unique property due to their high adsorption capacity and good catalytic activity. In this work the CaO nanocatalysts were prepared by hydrothermal method using anionic surfactant, sodium dodecyl sulphate (SDS), as a templating agent. The as-synthesized nanocatalysts were further used as substrate for the synthesis of alumina doped calcium oxide (Al2 O3 ·CaO) nanocatalysts via deposition-precipitation method at the isoelectric point of CaO. The Al2 O3 ·CaO nanocatalysts were characterized by FTIR, XRD, TGA, TEM, and FESEM techniques. The catalytic efficiencies of these nanocatalysts were studied for the photodegradation of 2, 4, 6-trinitrophenol (2, 4, 6-TNP), which is an industrial pollutant, spectrophotometrically. The effect of surfactant and temperature on size of nanocatalysts was also studied. The smallest particle size and highest percentage of degradation were observed at critical micelle concentration of the surfactant. The direct optical band gap of the Al2 O3 ·CaO nanocatalyst was found as 3.3 eV.